2017
DOI: 10.1111/pedi.12498
|View full text |Cite
|
Sign up to set email alerts
|

High HbA1c at onset cannot be used as a predictor for future metabolic control for the individual child with type 1 diabetes mellitus

Abstract: High HbA1c at onset was associated with high HbA1c during follow-up on a group level, but it cannot be used as a predictor of future metabolic control on an individual level. These results emphasize the important work done by the diabetes team in the first years after diagnosis. It is important to continuously set high goals for the achievement of tight metabolic control, in order to decrease the risk of microvascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Viswanathan et al (2011) showed that HbA1c levels at onset might predict future metabolic control, however, the study was relatively small (120 children) . Similar results were partly confirmed by Nilsson et al (2017) showing that high HbA1c at onset was associated with high HbA1c during follow‐up . A retrospective analysis from the UK showed that tracking of HbA1c values occurs at all levels of HbA1c, such that children who reach HbA1c target early in the course of the disease are more likely to continue with low HbA1c levels .…”
Section: Introductionmentioning
confidence: 90%
“…Viswanathan et al (2011) showed that HbA1c levels at onset might predict future metabolic control, however, the study was relatively small (120 children) . Similar results were partly confirmed by Nilsson et al (2017) showing that high HbA1c at onset was associated with high HbA1c during follow‐up . A retrospective analysis from the UK showed that tracking of HbA1c values occurs at all levels of HbA1c, such that children who reach HbA1c target early in the course of the disease are more likely to continue with low HbA1c levels .…”
Section: Introductionmentioning
confidence: 90%
“…17 In two previous studies conducted abroad, mean HbA1c at the time of diagnosis was found to be 11.6±2.6% and 10.6±4.4% in patients with type 1 DM. 18, 19 In a study conducted by Demir et al 20 in our country, HbA1c was found to be 10.5±2.6%. In a study conducted by Taşkın et al21, HbA1c was found to be 10.8±2.91.…”
Section: Discussionmentioning
confidence: 76%